2014
DOI: 10.1016/j.jocd.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Risk Assessment in Older Adults Using a Combination of Selected Quantitative Computed Tomography Bone Measures: A Subanalysis of the Age, Gene/Environment Susceptibility-Reykjavik Study

Abstract: Bone mineral density (BMD) and geometric bone measures are individually associated with prevalent osteoporotic fractures. Whether an aggregate of these measures would better associate with fractures has not been examined. We examined relationships between self-reported fractures and selected bone measures acquired by quantitative computerized tomography (QCT), a composite bone score, and QCT-acquired dual-energy X-ray absorptiometry–like total femur BMD in 2110 men and 2682 women in the Age, Gene/Environment S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Additionally, Black et al [34] found that for femoral neck integral volumetric density, the 5-year risk of hip fracture in the lowest quartile was >15 times that in the highest quartile (3.6 versus 0.2 %). Similarly, we have also found in our own material from the AGES-Reykjavik Study that vBMD predicts hip fractures in elderly men and women [36, 37]. The difference of 0.2 Z-scores (equal to 0.2 SD in vBMD) seen in the present study between individuals with high versus low frequency of milk intake in midlife is therefore likely to be of clinical relevance.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, Black et al [34] found that for femoral neck integral volumetric density, the 5-year risk of hip fracture in the lowest quartile was >15 times that in the highest quartile (3.6 versus 0.2 %). Similarly, we have also found in our own material from the AGES-Reykjavik Study that vBMD predicts hip fractures in elderly men and women [36, 37]. The difference of 0.2 Z-scores (equal to 0.2 SD in vBMD) seen in the present study between individuals with high versus low frequency of milk intake in midlife is therefore likely to be of clinical relevance.…”
Section: Discussionsupporting
confidence: 85%
“…33 Another strength of our study is the use of QCT measurements that have previously been shown to correlate well with DXA measurements as well as subsequent risk of fracture. 15,34 Furthermore, QCT measurements as opposed to DXA are not confounded by skeletal size and provide measurements from trabecular and cortical bone separately.…”
Section: Discussionmentioning
confidence: 99%
“…Low scores for the QCT measures vertebral trabecular BMD, femoral neck cortical thickness, and femoral neck trabecular BMD have been associated with increased risk of fractures in both men and women. 15 Two studies have used skeletal imaging techniques to compare bone disease in MGUS patients to matched controls. 16,17 In a study on 50 MGUS patients, compared with 100 controls, MGUS patients were found to have decreased BMD at the total femur, but no differences were found at other sites.…”
Section: Introductionmentioning
confidence: 99%
“…We measured volumetric QCT-BMD rather than areal BMD, but similar associations have been shown between fractures and BMD using these two measures [35] , [36] . Similar to many previous studies [3] , [12] we found a slight but significant positive trend between BMD in femoral neck and serum concentrations of 25(OH)D in both sexes.…”
Section: Discussionmentioning
confidence: 99%